(3cJGH aj GdYbGFO hYde GdcdGe Ydi ePGgH GdeYJRdIs - (3CHh GdMSf CMeO Hf eMeO Hf GdMSf Hf eMeO GdQUGU,J (B565 (3g` s ((3eMeO Hf eadM Hf YdGA s)
(3ChdgG (B:s
(3Chdg aUd ai Gfg dGjLhR Gf jchf eQjOkG ddeYGUi hGdNUGd gPG GdaUd HHGH GdYOd XGgQ s
(3BNQgG (B:s
(3gd jLhR Cf jbhd GfG eDef Ef TGA Gddg JYGdi hGdCUd ajg Gfg jLhR Hd dGjLhR NdGaI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeY GdcHjQ (B- (3UfYGA (B((3GdcJH GdUGOQg (B69) s
Keywords: (3GdJhMjO hGdedd hGdfMds